2020
DOI: 10.1371/journal.pone.0229325
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative anaemia might be a risk factor for postoperative delirium and prolonged hospital stay: A secondary analysis of a prospective cohort study

Abstract: Background Postoperative anaemia is a frequent surgical complication and in contrast to preoperative anaemia has not been validated in relation to mortality, morbidity and its associated health economic effect. Postoperative anaemia can predispose postoperative delirium through impairment of cerebral oxygenation. The aim of this secondary analysis is to investigate the association of postoperative anaemia in accordance with the sex specific World Health Organization definition of anaemia to postoperative delir… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 47 publications
6
39
0
Order By: Relevance
“…Post-operative anaemia is often a reflection of pre-operative work-up prior to surgery [1][2][3][4]. In addition.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Post-operative anaemia is often a reflection of pre-operative work-up prior to surgery [1][2][3][4]. In addition.…”
Section: Introductionmentioning
confidence: 99%
“…post-operative anaemia is also determined by co-morbidities of patients prior to surgery of which sepsis is a common example. [2] The prevalence of post-operative anaemia varies based on surgical specialties and the experience of the surgeon; prevalence rates of post-operative anaemia as high as 85.8% has been documented by Kunz et al in elective orthopaedic surgeries [2,5]. Furthermore, post-operative anaemia has closely been linked to increased post-operative morbidity, mortality and increased risk of peri-operative blood transfusion [1][2].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have shown that preoperative anaemia was considered a risk factor for the outcome in non-cardiac surgery; it was associated with a more extended hospital stay, a higher risk of perioperative complications, and higher mortality [35]. In a recent study of 800 patients undergoing elective noncardiac surgery, anaemia was associated with postoperative delirium and longer hospitalization [36]. The impact of preoperative anaemia on postoperative delirium in the cardiosurgical population is not yet well understood, and the results published so far have often been contradictory.…”
Section: Discussionmentioning
confidence: 99%